The methods of assessment of quality and safety of medicaments on the basis of low molecular weight heparins - E. A. Arianova; M. N. Bogachuk; O. I. Perederyaev (Сеченовский вестник, 2022)
To consider the methods for assessing quality and safety of drugs on the basis of low molecular weight heparin.